ANALISA KURVA PDD DAN PROFILE DOSE BERKAS ELEKTRON PESAWAT LINAC VARIAN CLINAC CX - Huswatun Hasanah; Nurul Qomariyah; I Wayan Ari Makmur; Rinarto Subroto; Rahadi Wirawan (Universitas Mataram, 2020)
Linac (linear Accelerator) is a radiotherapy device that utilizes radiation to kill cancer cells. Every radioterap equipment such as Linac aircraft must be calibrated periodically. One of them is monthly quality control which aims to test the performance of Linac so that the quality of the output of the radiation beam can be guaranteed. Quality control conducted is the measurement of Percentage Depth Dose (PDD) and Profile Dose. In PDD measurements, the Linac Variant Clinac CX electron beam (4, 6, 9, 12, and 15) MeV planes are used with a radiation field of 15 × 15 cm2. While the profile dose is measured in the radiation field 10 × 10 cm2 and 25 × 25 cm2 and using blue phantom, (referenc and field) detectors are equipped with computer control units (CCU) and carried out for crossline and inline directions at Dmax depth and certain depth with SSD 100 cm. The measurement results show the greater the electron energy used, the maximum dose (Dmax) obtained is getting smaller, conversely the greater the electron energy used, the greater the depth for the maximum dose. And the measurement results still meet the tolerance measurement that is ± 0.2. While the results of the Dose Profile measurements show a field area of 25 × 25 cm2 more flatness and symmetry than a 10 × 10 cm2 field area both inline and crosline directions and still meet measurement tolerances of ± 4.5% - ± 7% for flatness and ± 2 % for symmetry.